Cover Image, Volume 116, Number 9, September 2019. Issue 9 (1st August 2019) - Jorgolli, Marsela; Nevill, Tanner; Winters, Aaron; Chen, Irwin; Chong, Su; Lin, Fen‐Fen; Mock, Marissa; Chen, Ching; Le, Kim; Tan, Christopher; Jess, Philip; Xu, Han; et al.
Abstract : The cover image is based on the Review Nanoscale Integration of Single Cell Biologics Discovery Processes Using Optofluidic Manipulation and Monitoring by Marsela Jorgolli et al., https://doi.org/10.1002/bit.27024 .